A web-based system for automating the assessment question setting and associated activities for primary school mathematics : part F - Lyna Farhanah, Mohamed Foat (2014)
Education is an important aspect in the lives of each individual especially in Singapore where it starts as early as at the age of two or three. It is important to ensure that our education system is enhanced with the integration of technology to provide a better experience rather than the old-school method of using the hardcopy assessment books. The disadvantages of this assessment books are that the number of questions in each topic is limited.